2016
DOI: 10.1016/j.ijmultiphaseflow.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

String flash-boiling in gasoline direct injection simulations with transient needle motion

Abstract: A computational study was performed to investigate the influence of transient needle motion on gasoline direct injection (GDI) internal nozzle flow and near-field sprays. Simulations were conducted with a compressible Eulerian flow solver modeling liquid, vapor, and non-condensable gas phases with a diffuse interface. Variable rate generation and condensation of fuel vapor were captured using the homogeneous relaxation model (HRM). The non-flashing (spray G) and flashing (spray G2) conditions specified by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 48 publications
1
60
1
Order By: Relevance
“…Moon et al [69] have observed that multi-hole GDIs experience more pronounced transient fluctuations than diesel injectors, and propose that the low needle lift may be responsible for this phenomenon. Recent simulations [70] which reveal the complexity of the flow past the needle seat and in the sac support the hypothesis that GDIs exhibit strong and persistent transients in ROI under more realistic operating conditions. This is 175 supported by the observation that the transients can vary significantly between different injectors with the same nominal geometry, while the transients for a particular injector are highly repeatable during subsequent tests.…”
Section: Hydraulic and Mechanical Charaterizationmentioning
confidence: 69%
See 4 more Smart Citations
“…Moon et al [69] have observed that multi-hole GDIs experience more pronounced transient fluctuations than diesel injectors, and propose that the low needle lift may be responsible for this phenomenon. Recent simulations [70] which reveal the complexity of the flow past the needle seat and in the sac support the hypothesis that GDIs exhibit strong and persistent transients in ROI under more realistic operating conditions. This is 175 supported by the observation that the transients can vary significantly between different injectors with the same nominal geometry, while the transients for a particular injector are highly repeatable during subsequent tests.…”
Section: Hydraulic and Mechanical Charaterizationmentioning
confidence: 69%
“…• C and 70 20 MPa, as per Table 1. Evaporative, non-combusting conditions were desired, so an ambient at 573K / 300 • C and 6 bar was specified as the Spray G standard.…”
Section: The Spray G Injectormentioning
confidence: 99%
See 3 more Smart Citations